TRPV1 and PLC Participate in Histamine H4 Receptor-Induced Itch. (24th December 2015) - Jian, Tunyu; Yang, Niuniu; Yang, Yan; Zhu, Chan; Yuan, Xiaolin; Yu, Guang; Wang, Changming; Wang, Zhongli; Shi, Hao; Tang, Min; He, Qian; Lan, Lei; et al.
Abstract : Histamine H4 receptor has been confirmed to play a role in evoking peripheral pruritus. However, the ionic and intracellular signaling mechanism of activation of H4 receptor on the dorsal root ganglion (DRG) neurons is still unknown. By using cell culture and calcium imaging, we studied the underlying mechanism of activation of H4 receptor on the DRG neuron. Immepip dihydrobromide (immepip)—a histamine H4 receptor special agonist under cutaneous injection—obviously induced itch behavior of mice. Immepip-induced scratching behavior could be blocked by TRPV1 antagonist AMG9810 and PLC pathway inhibitor U73122. Application of immepip (8.3–50 μ M) could also induce a dose-dependent increase in intracellular Ca 2+ (C a 2 + i ) of DRG neurons. We found that 77.8% of the immepip-sensitized DRG neurons respond to the TRPV1 selective agonist capsaicin. U73122 could inhibit immepip-induced Ca 2+ responses. In addition, immepip-induced C a 2 + i increase could be blocked by ruthenium red, capsazepine, and AMG9810; however it could not be blocked by TRPA1 antagonist HC-030031. These results indicate that TRPV1 but not TRPA1 is the important ion channel to induce the DRG neurons' responses in the downstream signaling pathway of histamine H4 receptor and suggest that TRPV1 may be involved in the mechanism of histamine-induced itch response by H4 receptor activation.